Preparation and in-vitro and in-vivo Evaluation of Ayurvedic Formulation “Amruthotharam” Formulated by Classical and Modern Technique - Dhane, Ketaki; Gupta, Manish Kumar; Hyam, Supriya; Patil, Abhinandan (Indian Journal of Pharmaceutical Education and Research, 2023)
Glucose intolerance, central obesity, hypertension, and dyslipidemia are all part of the metabolic syndrome. Thus, a number of theories have been put out to explain the development of the metabolic syndrome, including an initial condition of insulin resistance that progressed to the other elements, with obesity serving as the primary initiator of the metabolic syndrome. Thus, it can be understood that metabolic syndrome is multi related and the basic cause is inflammation. Thus, while treating the metabolic syndrome the root cause needs to be targeted and for this the ayurvedic formulation is the best solution. Amruthotharam is one of such preparation which takes care of metabolic syndrome through inflammation. “Amruthotharam” is the combination is known as Kashayam was made from three main herbs whose efficacy in treating indigestion and other stomach-related issues has been demonstrated in several cases. Three parts of Tinospora cordifolia, two parts of Terminalia chebula, and one part of Zingiber officinale are combined to create the mixture. The present study is focusing on the comparisons between the Amruthotharam a kerealian Ayurvedic medicine formulated by classical and modern technique which can be evaluated analytically and pharmacologically.
Keywords: Metabolic syndrome; Amruthotharam; Immunomodulatory